2020
DOI: 10.2147/oaem.s244110
|View full text |Cite
|
Sign up to set email alerts
|

<p>Traditional Chinese Medicine in Emergency Treatment Mechanism and Application</p>

Abstract: Traditional Chinese medicine has usually been recognized to be efficacious to treat chronic diseases from the western point-of-view. However, there is a long history in China of applying traditional Chinese medicine in many acute and urgent medical conditions. In this review, selected methods documented in traditional Chinese medicine including blowing air to ear, nose insufflating therapy, acupuncture and moxibustion were presented as the common practices to promote consciousness recovery from coma. We aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…It is essential that physicians are able to distinguish the benign forms of urticaria and angioedema from potentially severe and life-threatening conditions, particularly when first visiting a newly admitted patient [ 7 ]. In emergency rooms as well as outpatient clinics, a combined interventional approach drawing from both conventional and complementary medicine could assist recovery and improve survival in affected patients [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential that physicians are able to distinguish the benign forms of urticaria and angioedema from potentially severe and life-threatening conditions, particularly when first visiting a newly admitted patient [ 7 ]. In emergency rooms as well as outpatient clinics, a combined interventional approach drawing from both conventional and complementary medicine could assist recovery and improve survival in affected patients [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown the important role of these therapies in the treatment of various diseases [ 53 - 56 ]. In contrast, very few studies have explored the role of TCM, especially PM, in the prevention and treatment of life-threatening diseases that need immediate care [ 40 , 41 ]. Meng et al found that, although Traditional Chinese medicine is widely recognized as effective in treating chronic diseases, some TCM therapies like blowing air to the ear, nose insufflating therapy, acupuncture, and moxibustion are potent in many acute and urgent medical conditions [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The whole prescription can reinforce qi, strengthen the spleen, calm the liver, and reinforce the kidney [ 23 28 ]. Recent research has reported that Atractylodes macrocephala and Poria cocos can enhance human immunity [ 29 , 30 ]. Uncaria rhynchophylla and Eucommia ulmoides have strong antihypertensive, sedative, spasmodic, and diuretic effects [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%